Newly graduated nurses' empowerment regarding professional competence and other work-related factors. - Kuokkanen L; Leino-Kilpi H; Numminen O; Isoaho H; Flinkman M; Meretoja R (United Kingdom, 2025)
BACKGROUND Although both nurse empowerment and competence are fundamental concepts of describing newly graduated nurses' professional development and job satisfaction, only few studies exist on the relationship between these concepts. Therefore, the purpose of this study was to determine how newly graduated nurses assess their empowerment and to clarify professional competence compared to other work-related factors. METHODS A descriptive, cross-sectional and correlational design was applied. The sample comprised newly graduated nurses (n = 318) in Finland. Empowerment was measured using the 19-item Qualities of an Empowered Nurse scale and the Nurse Competence Scale measured nurses' self-assessed generic competence. In addition to demographic data, the background data included employment sector (public/private), job satisfaction, intent to change/leave job, work schedule (shifts/business hours) and assessments of the quality of care in the workplace. The data were analysed statistically by using Spearman's correlation coefficient as well as the One-Way and Multivariate Analysis of Variance. Cronbach's alpha coefficient was used to estimate the internal consistency. RESULTS Newly graduated nurses perceived their level of empowerment and competence fairly high. The association between nurse empowerment and professional competence was statistically significant. Other variables correlating positively to empowerment included employment sector, age, job satisfaction, intent to change job, work schedule, and satisfaction with the quality of care in the work unit. The study indicates competence had the strongest effect on newly graduated nurses' empowerment. CONCLUSIONS New graduates need support and career opportunities. In the future, nurses' further education and nurse managers' resources for supporting and empowering nurses should respond to the newly graduated nurses' requisites for attractive and meaningful work.